Intercorporeal Design: Dissolving Self-Other Dualism in Interaction Design - Stepanova, Ekaterina R.; Riecke, Bernhard E. (ACM, 2024)
Historically, technology and interaction design evolved from an information-processing paradigm of the human mind rooted in mind-body dualism. Technologies for social interaction followed a sender-receiver model, mediating the decoding of messages between sender and receiver. Dissolving mind-body dualism, Embodied Interaction and Somatic Turn in HCI offered a paradigmatic shift, prioritizing the role of our acting and sensing bodies in the interaction. We extend this move by proposing Intercorporeal Design. Intercorporeal Design dissolves not only mind-body dualism but also self-other dualism, guiding us to design holistically for the dynamic co-experienced interaction encompassing multiple bodies and their shared environment. We suggest three provisional design pillars that could help realize intercorporeal design: closing the action-perception loop, designing for the felt experience, and considering human bodies as a design material. Finally, we review selected examples of intercorporeal designs to illustrate how this design stance can be embodied in interaction design artifacts. Intercorporeal design is an evolving design stance, which could allow us to dissolve self-other boundary and invite harmonious experiences of interbodily resonance.
Keywords: Riecke; Riecke_2024; bernhard-riecke; conferencePaper; katerina-stepanova; thesis-related